Philippine dances [videorecording] - National Commission for Culture and the Arts (Quezon City : Felta.)
A television program featuring the history and development of Philippine dances as performed by the Ramon Obusan Folklore Dance Group.
Keywords: Dance -- Philippines -- History; Folk dancing -- Philippines